A flexible heterogeneous real-time digital image correlation system - Wang, Tianyi (2020)
An accurate and flexible real-time digital image correlation (RT-DIC) system utilizing a pipelined CPU and GPU parallel computing framework is proposed. First, the respective advantages of CPU and GPU in performing the fast Fourier transform-based cross-correlation (FFT-CC) algorithm and the inverse-compositional Gauss Newton (IC-GN) algorithm of the employed path-independent DIC (PI-DIC) method are elucidated. Second, based on the different properties and performances of CPU and GPU, a pipelined system framework unifying five Variants of combinations of CPU and GPU is proposed, which can be flexibly applied to various practical applications with different requirements of measurement scales and speeds. Last, both the accuracy and speed of the entire pipelined framework are verified by a PC implementation of the RT-DIC system integrating Variants 2–5. Variants 2 and 5 are also implemented on an iPhone 5S for the feasibility investigation of realizing a portable RT-DIC system on mobile devices using the same framework.